2014
DOI: 10.1088/0953-2048/27/8/085005
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial strain dependence of the critical current of DI-BSCCO tapes

Abstract: In order to explain the effect of uniaxial strain on the critical current of DI-BSCCO-Bi2223 tapes, we employed a springboard sample holder that can smoothly and continuously apply both tensile and compressive strains to tape samples. Over a narrow tensile strain region, the critical current in the tapes decreased linearly with increasing strain and returned reversibly with decreasing strain. When compressive strain was applied, the critical current first increased and then reached a weak maximum. Thereafter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
2
20
2
Order By: Relevance
“…Besides, pre-tension technique leads to extra compressive strains on the filaments. It has been reported that I c performances tends to drop more rapidly in the compressive strain than in the tensile strain on Type HT-CA wires [13], Type H, and Type HT-SS wires [14]. As seen in Fig.…”
Section: E I C −B−t Performancesmentioning
confidence: 76%
“…Besides, pre-tension technique leads to extra compressive strains on the filaments. It has been reported that I c performances tends to drop more rapidly in the compressive strain than in the tensile strain on Type HT-CA wires [13], Type H, and Type HT-SS wires [14]. As seen in Fig.…”
Section: E I C −B−t Performancesmentioning
confidence: 76%
“…However there is also a non-negligible bending strain because of the finite thickness of tape. However, as discussed previously [11], the contribution from the bending strain component was not considered in the present study, because its influence is quite limited. Because the strain gauge is further from the neutral axis of the springboard than the REBCO layer, caused by the thickness of the Cu lamination, the thickness of the glue for the strain gauge and the half-thickness of the strain gauge itself, the measured strain has been corrected by multiplying a factor k. The procedure to evaluate the factor k is explained in Appendix A.…”
Section: Definitions Of Terms Used To Characterize the Local Strainmentioning
confidence: 99%
“…For practical REBCO and BSCCO wires, a maximum in the critical current has also been observed in the strain dependence. In studies to date, Ap tended to be inconsistent with Aff [10,11]. It is the aim of this work to understand better the true nature of the critical current maximum and its dependence on strain by explicitly examining directly, the change of critical current as a function of local strain exerted on the SC component.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to achieve the high current densities that are required to allow for sufficient margin for adding reinforcement to the mechanically relatively weak conductor, the reaction needs to take place at 25 to 100 bar in an oxygen-inert gas mixture [13, 26] (figure 1). There is presently discrepancy in the literature on whether densification of the Bi-2212 by overpressure reaction improves the allowable longitudinal strain limit beyond the 0.3 to 0.4% that is commonly observed in Ag/Ag-alloy matrix Bi-2212 and Bi-2223 wires and tapes [27, 28, 29, 30, 31, 32, 33, 34, 35]: Substrate-based experiments suggest no improvement and a 0.3% – 0.4% strain limit, whereas tensile tests suggest a 0.6% strain limit [36, 37, 38, 39]. That Bi-2212 is mechanically-weaker than both REBCO and high-strength Bi-2223 (below) is clear and there are recent attempts to diffusion-bond high-strength materials to aspected Bi-2212 wires to improve the allowable tensile stress from 120 to 150 MPa [39, 40] to more than 400 MPa [40].…”
Section: Introductionmentioning
confidence: 99%